A Byzantine book on dream interpretation : the Oneirocriticon of Achmet and its Arabic sources - Mavroudi, Maria V. (The medieval Mediterranean ;, 2002)
This volume discusses the so-called Oneirocriticon of Achmet , the most important Byzantine work on dream interpretation which was written in Greek in the 10th century and has greatly influenced subsequent dreambooks in Byzantine Greek, Medieval Latin, and modern European languages. By comparing the Oneirocriticon with the 2nd-century A.D. dreambook of Artemidoros (translated into Arabic in the 9th century) and five medieval Arabic dreambooks, this study demonstrates that the Oneirocriticon is a Christian Greek adaption of Islamic Arabic material and that the similarities between it and Artemidoros are due to the influence of Artemidoros on the Arabic sources of the Byzantine work. The Oneirocriticon 's textual tradition, its language, the identities of its author and patron, and its position among other Byzantine translations from Arabic into Greek are also investigated.